ANALISIS ANALISIS KESULITAN MEMBACA PADA SISWA KELAS II SEKOLAH DASAR NEGERI 3 CIRACAP - Siti Sa'diah; Lisna Wati; Novita Fitriani; Atot Sugiri; Soleh Iskandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to identify and describe the reading difficulties experienced by second-grade students of State Elementary School 3 Ciracap, the factors causing these difficulties, and the teacher’s efforts to overcome them. This study employed a qualitative approach with a descriptive research design. The research participants consisted of second-grade students of State Elementary School 3 Ciracap and the second-grade teacher as the main informant. Data were collected through observation, interviews, and documentation. The collected data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings showed that several students still experienced reading difficulties, including recognizing and distinguishing similar letters, reading hesitantly, spelling letters one by one, and combining letters into syllables and words. In addition, some students had difficulty understanding simple reading texts. These difficulties were influenced by internal and external factors. Internal factors included low interest in reading, limited ability to remember letters, and low learning readiness. External factors included limited parental assistance at home, lack of reading practice, and differences in students’ educational backgrounds. To address these difficulties, the teacher implemented several strategies, such as daily reading activities, reading aloud in turns, individual guidance, and the use of Bacalah Books 1–3 during reading instruction. Based on the findings, it can be concluded that the reading difficulties experienced by second-grade students of State Elementary School 3 Ciracap were influenced by various internal and external factors. Therefore, cooperation between teachers and parents is needed to support the improvement of students’ reading skills.